The effect of a paramagnetic metal ion within a molecule: comparison of the structurally identical paramagnetic [3, 3-Fe(1, 2-C2B9H11)2]− with the diamagnetic [3, 3-Co(1, 2-C2B9H11)2]− sandwich complexes. Issue 6 (16th December 2014) - Cioran, Ana M.; Teixidor, Francesc; Viñas, Clara
Abstract : Effects on the NMR spectra of a paramagnetic metal ion are clearly observed by comparing identical sandwich molecular structures of diamagnetic [3, 3′-Co(1, 2-C2 B9 H11 )2 ] − with paramagnetic [3, 3′-Fe(1, 2-C2 B9 H11 )2 ] − . Abstract : Derivatives of the ferrabisdicarbollide [3, 3′-Fe(1, 2-C2 B9 H11 )2 ] − have been produced starting from the zwitterion [3, 3′-Fe(8-(OCH2 CH2 )2 -1, 2-C2 B9 H10 )(1′, 2′-C2 B9 H11 )], 1, upon reaction with nucleophiles: alkoxides, halides and hydrosulfide ions HS − . The result has been the preparation of [3, 3′-Fe(8-(OCH2 CH2 )2 R /X -1, 2-C2 B9 H10 )(1′, 2′-C2 B9 H11 )] (R = OMe, [2 ] − ; OEt, [3 ] − ; OCH2 CH2 OCH3, [4 ] − ; andX = Cl, [5 ] − ; Br, [6 ] − ; I, [7 ] − ; and SH, [8 ] − ). The reaction behavior of1 is comparable to the well-studied cobalt equivalent, [3, 3′-Co(8-(OCH2 CH2 )2 -1, 2-C2 B9 H10 )(1′, 2′-C2 B9 H11 )], and the yields and stability of the resulting complexes are similar. These results are relevant taking into account that [3, 3′-Fe(1, 2-C2 B9 H11 )2 ] − is a paramagnetic anion. Implications of this are observed in the 11 B-, 1 H and 13 C NMR spectra of [3, 3′-Co(1, 2-C2 B9 H11 )2 ] − and [3, 3′-Fe(1, 2-C2 B9 H11 )2 ] − that having identical sandwich molecular structures and the same negative charge have absolutely different widths of the NMR field, between 15 and −25 ppm for [3, 3′-Co(1, 2-C2 B9 H11 )2 ] − and in the range 150 to −550 ppm for [3, 3′-Fe(1, 2-C2 B9 H11 )2 ] − . The sharpness of both spectra is on the other hand comparable, although no B–H couplings are observed in the Fe metallacarborane or its derivatives. Remarkable is the comparative influence vs . [3, 3′-Co(1, 2-C2 B9 H11 )2 ] − of replacing Co by Fe on the elements of the cluster layer nearest to the metal. The two equivalent C cluster (Cc ) atoms are influenced at 36 840 Hz, the two equivalent B atoms that are adjacent to the two Cc are influenced at 38 157 Hz and the single B that is adjacent to the two B atoms is influenced at 44 062 Hz. Remarkable is the similar influence on B and on C, taking into account that the values have been obtained from two distinct NMR spectra of 11 B and 13 C. The { 11 B– 11 B} COSY NMR and { 1 H– 11 B} HETEROCOSY NMR spectra of [3, 3′-Fe(1, 2-C2 B9 H11 )2 ] − have been obtained and are reported for the first time.